Solid‐phase extraction methods for nucleic acid separation. A review. Issue 1 (8th September 2021) - Li, Peipei; Li, Menghang; Yue, Dongmei; Chen, Haixia
Abstract: The separation and purification of biomacromolecules such as nucleic acid is a perpetual topic in separation processes and bioengineering (fine chemicals, biopharmaceutical engineering, diagnostics, and biological characterization). In principle, the solid‐phase extraction for nucleic acid exhibits efficient phase separation, low pollution risk, and small sample demand, compared to the conventional liquid‐phase extraction. Herein, solid‐phase extraction methods are systematically reviewed to outline research progress and explore additional solid‐phase sorbents and devices for novel, flexible, and high‐efficiency nucleic acid separation processes. The functional materials capture nucleic acid, magnetic and magnetic‐free solid‐phase extraction methods, separation device design and optimization, and high‐throughput automatable applications based on high‐performance solid‐phase extraction are summarized. Finally, the current challenges and promising topics are discussed.